Pituitary coma with continuing menstruation. Issue 630 (April 1978) - Mitchell, D. M.; Webb, S. C.; Hoffbrand, B. I.
Abstract : A case of pituitary coma with continuing menstruation is presented. This association is extremely rare, but a history of recent menstrual periods does not exclude advanced hypopituitarism from the differential diagnosis of severe hyponatraemia.